Electrochemistry and Spectroelectrochemistry with Electrospun Indium Tin Oxide Nanofibers. (1st June 2016) - Mierzwa, Maciej; Lamouroux, Emmanuel; Vakulko, Ivan; Durand, Pierrick; Etienne, Mathieu
Graphical abstract: Highlights: Preparation of transparent and conductive ITO nanofibers. Diameter between 110 and 235 nm and thickness between 12 and 120 μm. Electroanalysis of ascorbic acid with 1.04 mA mM −1 cm −2 sensitivity. Transparency up to 35% at 800 nm with 34 μm thick layer. Application to spectroelectrochemistry of Prussian blue. Abstract: In this work, Indium tin oxide (ITO) nanofiber materials have been prepared and subsequently used for electrochemical and spectroelectrochemical analysis. Nanofibers have been electrospun from a suspension of polyvinylpyrrolidone (PVP) and indium and tin precursors with a ratio Sn/In = 0.16. Their diameter could be adjusted between 110 and 235 nm and the layer thickness was controlled between 12 and 120 μm. A calcination at 500 °C in air followed by a thermal treatment at 1000 °C under nitrogen atmosphere allowed to obtain conductive ITO nanofibers. XRD characterizations confirmed the successful transition of the starting material into indium tin oxide, showed the influence of the thermal treatment on grain size and provided some insight on their orientation. The electrochemical properties of the nanofibers have been characterized and optimized using dimethanolferrocene as a model probe. This porous ITO electrode have been applied to the electroanalysis of ascorbic acid with a sensitivity of 1.04 mA mM −1 cm −2 and to spectroelectrochemistry using Prussian blue as model system.